Effects of two different inspiratory muscle training devices on respiratory muscle strength, cardiopulmonary functional capacity, and quality of life of COPD patients - Oliveira, Kelly Cristina da Silva; do Nascimento Breda, Melissa; Ricardo Pepe Ambrozin, Alexandre (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Inspiratory muscle weakness is one of the complications of chronic obstructive pulmonary disease (COPD). This condition has been minimized by inspiratory muscle training (IMT). Still, different IMT devices need to be compared to identify the best option. Objective: To evaluate the effects of two IMT devices on respiratory muscle strength, cardiorespiratory functional capacity, and life quality of COPD patients. Method: Before and after the IMT protocol, 17 patients were submitted to manovacuometry, six-minute walk test (6MWT), and questionnaire from the Saint George Hospital in Respiratory Disease (SGRQ) for inspiratory muscle strength, cardiorespiratory functional capacity, and life quality assessments, respectively. Afterwards, they were divided into two groups to perform IMT for four weeks, one by Threshold® IMT (IMTG) and the other by POWERbreathe® Classic (PG). Results: Maximal inspiratory pressure increased significantly from -62.00±16.03 to -75.55±22.84 cmH2O in IMTG, and from -56.00±22.01 to -71.25±27.67 cmH2O in PG. The distance covered in the 6MWT clinically increased with both IMTG and PG. The SGRQ answers showed improvements in all domains evaluated for both groups. However, the intergroup results showed no statistically significant differences. Conclusion: Both IMT devices increased inspiratory muscle strength, improved life quality, and optimized cardiorespiratory functionality in COPD patients. None was superior to the other for the analyzed parameters.